2008
DOI: 10.5132/jbse.2008.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Cymatium parthenopeum parthenopeum (von Salis, 1793) (Mesogastropoda: Ranellidae): A New Bioindicator of Organotin Compounds Contamination?

Abstract: This work reports the occurrence of imposex in the mesogastropod Cymatium parthenopeum parthenopeum in the coast of Espírito Santo (Southeastern Brazil) and evaluates the possible use of this species as a bioindicator of organotins (OTs) contamination. A total of 53 adult specimens were sampled at Formosa beach nearby the Vitoria main marina, which is a critical area for this kind of contamination. The animals were analyzed using a non-destructive protocol and a sub-sample of 7 animals (6 imposexed females and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Gastropods populations of S. haemastoma, Cymathium parthenopeum and Leucozonia nassa from Cabo Frio (Rio de Janeiro state; Castro et al 2007c); Nassarius vibex from Itacuruça island (Rio de Janeiro) (Cardoso et al 2009), the endemic marine snail Voluta ebraea (Castro et al 2008) andN. vibex (Lima-Verde et al 2010) from Ceará state; and C. partenopeum, T. deltoidea and L. nassa from Espirito Santo state (Costa et al 2009) were reported as impacted.…”
Section: Imposex In the Brazilian Coastmentioning
confidence: 97%
“…Gastropods populations of S. haemastoma, Cymathium parthenopeum and Leucozonia nassa from Cabo Frio (Rio de Janeiro state; Castro et al 2007c); Nassarius vibex from Itacuruça island (Rio de Janeiro) (Cardoso et al 2009), the endemic marine snail Voluta ebraea (Castro et al 2008) andN. vibex (Lima-Verde et al 2010) from Ceará state; and C. partenopeum, T. deltoidea and L. nassa from Espirito Santo state (Costa et al 2009) were reported as impacted.…”
Section: Imposex In the Brazilian Coastmentioning
confidence: 97%
“…The Espirito Santo Bay has intense maritime traffic due to the presence of ports and marinas in the region and has been monitored since 2007 with the species Stramonita haemastoma (unpublished data), Thais deltoidea (Costa et al, 2008a), Cymatium parthenopeumparthenopeum (Costa et al, 2008b), Leucozonia nassa and L. ocellata (Costa et al, 2014). This region has high levels of TBT and its metabolites were detected (Costa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Other species are also being used in biomonitoring programs, such as Thais deltoidea (Costa et al, 2008a), Cymatium parthenopeumparthenopeum (Costa et al, 2008b), Nassarius vibex (Cardoso et al, 2010) and species of the family Fasciolariidae, including Leucozonia nassa and Leucozonia ocellata (Costa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the Brazilian coast, particularly in recent years, imposex associated to TBT has been reported in the southern (Castro et al 2012a), southeastern (Fernandez et al 2005;Quadros et al 2009;Costa et al 2009;Cardoso et al 2009;Borges et al 2013), and northeastern regions (Camillo et al 2004;Castro et al 2004;Castro et al 2007a, b;Fernandez et al 2007;Castro et al 2008;Lima-Verde et al 2010;Azevedo et al 2012). However, most of these studies have focused on rocky-shore species such as Stramonita haemastoma, Stramonita rustica, Thais deltoidea, Leucozonia nassa, Leucozonia ocelata, Cymatium parthenopeum, Voluta ebraea, Pisania auritula, among others (Castro et al 2012a).…”
Section: Introductionmentioning
confidence: 91%